A new class of composition operators - S. Pattanayak; C. K. Mohapatra; A. K. Mishra (International Journal of Mathematics and Mathematical Sciences)
A new class of composition operators Pϕ:H2(T)→H2(T), with ϕ:T→D¯ is introduced. Sufficient conditions on ϕ for Pϕ to be bounded and Hilbert-Schmidt are obtained. Properties of Pϕ with ϕ(eit)=aeit+be−it for different values of the parameters a and b have been investigated. This paper concludes with a discussion on the compactness of Pϕ.